A Novel Opportunistic Spectrum Sharing Scheme for Cognitive Ad Hoc Networks - Kalil, Mohamed; Liers, Florian; Volkert, Thomas; Mitschele-Thiel, Andreas (Electronic Communications of the EASST, 2009)
Nowadays, wireless ad hoc networks are using a static spectrum allocation which leads to congestion in this spectrum parts as the number of devices increases. On the contrary, a significant portion of the spectrum in licensed band (e.g. TV band) is not utilized. Cognitive radio (CR) is a promising technology to solve the spectrum inefficiency problem in ad hoc networks. Based on CR, the unlicensed (secondary) users will utilize the unused spectrum of the licensed (primary) users in an opportunistic manner. As a result, the average spectrum usage will be increased. However, the sudden appearance of primary users will have a negative impact on the performance of secondary users, since secondary users must evacuate the occupied channel and handoff to another unutilized one. This process continues till an unlicensed user finishes his transmission. We will name this process consecutive spectrum handoff (CSH). In order to increase the performance of CR, the number of consecutive spectrum handoffs should be reduced. In this paper, a novel opportunistic spectrum sharing scheme under a heterogeneous spectrum environment of licensed and unlicensed bands is introduced. In this scheme, the licensed channels will be used as operating channels and the unlicensed channels will be used as backup channels when the primary user appears. Since the unlicensed channels are not interrupted by primary users, no more spectrum handoff is needed.